2023
DOI: 10.1021/jacs.3c04162
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Inhibition of Heparanases and β-Glucuronidases by Siastatin B

Yurong Chen,
Adrianus M. C. H. van den Nieuwendijk,
Liang Wu
et al.

Abstract: Siastatin B is a potent and effective iminosugar inhibitor of three diverse glycosidase classes, namely, sialidases, β-D-glucuronidases, and N-acetyl-glucosaminidases. The mode of inhibition of glucuronidases, in contrast to sialidases, has long been enigmatic as siastatin B appears too bulky and incorrectly substituted to be accommodated within a β-D-glucuronidase active site pocket. Herein, we show through crystallographic analysis of protein-inhibitor complexes that siastatin B generates both a hemiaminal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Heparastatin (SF4), a compound optimized for inhibition of Hpse enzymatic activity, is a derivative of a bacterial product siastatin B that can inhibit the enzymatic activity of Hpse. The complex structure of human Hpse and siastatin B was recently demonstrated using 3D crystallography [ 55 ]. That study identified amino acid residues that are involved in the interaction of Hpse with siastatin B.…”
Section: Discussionmentioning
confidence: 99%
“…Heparastatin (SF4), a compound optimized for inhibition of Hpse enzymatic activity, is a derivative of a bacterial product siastatin B that can inhibit the enzymatic activity of Hpse. The complex structure of human Hpse and siastatin B was recently demonstrated using 3D crystallography [ 55 ]. That study identified amino acid residues that are involved in the interaction of Hpse with siastatin B.…”
Section: Discussionmentioning
confidence: 99%